2014
DOI: 10.1007/s00204-014-1219-5
|View full text |Cite
|
Sign up to set email alerts
|

The Ca2+-calmodulin-Ca2+/calmodulin-dependent protein kinase II signaling pathway is involved in oxidative stress-induced mitochondrial permeability transition and apoptosis in isolated rat hepatocytes

Abstract: Oxidative stress (OS) is a common event in most hepatopathies, leading to mitochondrial permeability transition pore (MPTP) formation and further exacerbation of both OS from mitochondrial origin and cell death. Intracellular Ca²⁺ increase plays a permissive role in these events, but the underlying mechanisms are poorly known. We examined in primary cultured rat hepatocytes whether the Ca²⁺/calmodulin (CaM)-dependent protein kinase II (CaMKII) signaling pathway is involved in this process, by using tert-butyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 73 publications
(87 reference statements)
2
26
0
Order By: Relevance
“…The results showed indeed an increased GSSG extrusion in BZL-treated cells that was prevented by the MRP2 inhibitor MK571. GSSG efflux was not increased when cells were only incubated with tBOOH, a situation resembling ROS and GSSG increases by BZL (Toledo et al 2014) but not associated to MRP2 induction (unpublished results). Thus, enhanced MRP2 expression and not higher substrate availability seems to play the most important role in GSSG clearance in conditions of BZL-triggered oxidative stress.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The results showed indeed an increased GSSG extrusion in BZL-treated cells that was prevented by the MRP2 inhibitor MK571. GSSG efflux was not increased when cells were only incubated with tBOOH, a situation resembling ROS and GSSG increases by BZL (Toledo et al 2014) but not associated to MRP2 induction (unpublished results). Thus, enhanced MRP2 expression and not higher substrate availability seems to play the most important role in GSSG clearance in conditions of BZL-triggered oxidative stress.…”
Section: Discussionmentioning
confidence: 80%
“…Only DMSO (0.1% v/v) was added to control cells (C). Tert-butyl hydroperoxide (tBOOH, 500 μM, 15 min) was used as a positive control of reactive oxygen species (ROS) generation (Toledo et al 2014). The concentration-dependence of BZL effects on intracellular redox status was evaluated incubating the cells with BZL 50, 100 and 200 μM for 24 h. Then, glutathione levels were quantified as described below.…”
Section: Methodsmentioning
confidence: 99%
“…Accumulating evidence has implicated that transient receptor potential canonical 3 is responsible for the increase in Ca 2+ /calmodulin-dependent kinase II (CaMKII) activity and ROS production (Kitajima et al 2011). Further study showed that mitochondrial ROS generation was mediated by Ca 2+ /CaM/CaMKII signaling pathway (Toledo et al 2014). We speculate that the increased ROS formation might be via Ca 2+ /CaM/CaMKII signaling pathway which is elicited by TRPA1 activation induced by cold stimulation.…”
Section: Production Of Reactive Oxygen Species Is Through the Activatmentioning
confidence: 75%
“…However, it remains to be studied, whether these changes represent primary events caused by copper or whether they are consequences of copper-induced oxidative stress (Gaetke et al 2014). Currently neurotoxicity (Balmer et al 2014;Zimmer et al 2014;Krug et al 2013;Leist et al 2013;Krause et al 2013), hepatotoxicity (Campos et al 2014Liu et al 2014;Godoy et al 2009Godoy et al , 2013Godoy et al , 2015Schyschka et al 2013;Schliess et al 2014;Grinberg et al 2014;Ghallab 2013Ghallab , 2014a and control mechanisms of oxidative stress (Møller et al 2014;Lim et al 2014;Finazzi and Arosio 2014;Wu et al 2014;Toledo et al 2014;Li Volti et al 2006) represent cutting-edge topics in toxicology. The present review of Gaetke and colleagues is particularly interesting for everyone involved in these fields of research.…”
Section: Riveramentioning
confidence: 99%